Simulation study of a dense polymeric catalytic membrane reactor with plug-flow pattern - José M. Sousa (2003)
A theoretical study on a tubular membrane reactor, assuming isothermal operation, plug-flow pattern and using a dense polymeric catalytic membrane, is performed. The reactor conversion for an Areversible arrowB equilibrium gas-phase reaction is analyzed, considering the influence of the reactants and products diffusion and sorption coefficients, the influence of the total pressure gradient and the influence of the ratio between the membrane thickness and its internal radius as well as the influence of the feed location (tube side or shell side) and the co-current. counter-current and cross-flow operation modes. One of the most unexpected conclusion is that for a set of conditions where the co-current and counter-current flows leads to differences in the reactor performance, the co-current flow is always better than the counter-current flow, exactly the reverse of what takes place when the membrane performs only gas separation. It is also concluded that the relative permeate pressure favors or penalizes the conversion, depending on the relative permeabilities of each reaction component. It is also concluded that the best reactor's feed location and the optimum r(1)/delta ratio depend on the relative sorption and diffusion coefficients of the reaction components as well as on the range of the Thiele modulus and contact time operation values.